The healing power of spirituality : how faith helps humans thrive - Ellens, J. Harold, 1932- (Psychology, religion, and spirituality., 2009)
This three-volume set addresses how the role of spirituality and its constructive expressions in various religions-and outside of formal religion-enhances human personality and experience.